The Social Vulnerability Index and Long-term Outcomes After Traumatic Injury. Issue 1 (12th July 2022) - Herrera-Escobar, Juan P.; Uribe-Leitz, Tarsicio; Wang, Joyce; Orlas, Claudia P.; Moheb, Mohamad El; Lamarre, Taylor E.; Ahmad, Niha; Hau, Ka Man; Jarman, Molly; Levy-Carrick, Nomi C.; Sanchez, Sabrina E.; Kaafarani, Haytham M. A.; et al.
Abstract : Objective: The aim of this study was to evaluate the Social Vulnerability Index (SVI) as a predictor of long-term outcomes after injury. Background: The SVI is a measure used in emergency preparedness to identify need for resources in the event of a disaster or hazardous event, ranking each census tract on 15 demographic/social factors. Methods: Moderate-severely injured adult patients treated at 1 of 3 level–1 trauma centers were prospectively followed 6 to 14 months post-injury. These data were matched at the census tract level with overall SVI percentile rankings. Patients were stratified based on SVI quartiles, with the lowest quartile designated as low SVI, the middle 2 quartiles as average SVI, and the highest quartile as high SVI. Multivariable adjusted regression models were used to assess whether SVI was associated with long-term outcomes after injury. Results: A total of 3153 patients were included [54% male, mean age 61.6 (SD = 21.6)]. The median overall SVI percentile rank was 35th (IQR: 16th–65th). compared to low SVI patients, high SVI patients were more likely to have new functional limitations [odds ratio (OR), 1.51; 95% confidence interval (CI), 1.19–1.92), to not have returned to work (OR, 2.01; 95% CI, 1.40–2.89), and to screen positive for post-traumatic stress disorder (OR, 1.56; 95% CI, 1.12–2.17). Similar results were obtained when comparing average with low SVI patients, with average SVI patients having significantly worse outcomes. Conclusions: The SVI has potential utility in predicting individuals at higher risk for adverse long-term outcomes after injury. This measure may be a useful needs assessment tool for clinicians and researchers in identifying communities that may benefit most from targeted prevention and intervention efforts.